IMPROVING PURCHASING DECISIONS THROUGH TRUST AND ELECTRONIC WORD OF MOUTH AS INTERVENING VARIABLES IN ONLINE SHOPPING - Yuliana, Rahmi; Hamdani, Muliawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to analyze and dig deeper into the concept of purchasing decisions by using trust variables and electronic word of mouth variables as intervening variables. The phenomenon of consumer behavior related to e-commerce will be said to increase with the high growth of internet users, where the total internet users in Indonesia are predicted to reach 72.8 million people, which overall ranks third in the Asean region. The increase in the number of internet technology users has an impact on online shopping behavior among consumers. However, this is inversely proportional to offline retail sales which have experienced a setback, marked by the lack of consumers in shopping centers. This has made the situation of out-of-network retail in Indonesia worse, marked by (1) changes in consumer behavior, (2) reduced employment opportunities (3) Increased number of online stores. The data for this research uses primary data, namely by taking direct samples of respondents who have shopped online at three marketplaces, Tokopedia and Lazada in Indonesia. The data analysis techniques used are descriptive analysis and inferential analysis. Then the data is processed using Smart PLS software to test the hypothesis that there is a significant influence between exogenous variables and endogenous variables. The results of this research will be able to find out how big the influence is.